Impact of COVID-19 Infection on Outcome of Cardiac Surgery patients in Tertiary Cardiac Care Hospital - Sobia, Farah; Paracha, Vaqar Ilahi; Waseem, Muhammad; Umer, Raja; Nawaz, Atif (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine the impact of COVID-19 infection on outcome of cardiac surgery patients.Study Design: Comparative Cross-sectional study.Place and Duration of Study: Cardiac Surgery Department, Armed Forces Institute of Cardiology/National Institute of Heart Diseases, Rawalpindi Pakistan, from Jul 2020 to Jun 2022.Methodology: All patients who underwent cardiac surgery were included. 1370 patients were recruited through nonprobability consecutive sampling, which were further divided into three groups depending upon the COVID-19 infection as no COVID-19, post COVID-19 and active COVID-19 infection groups. The groups were compared for in-hospital mortality and morbidity of the cardiac surgery. Descriptive and inferential statistics were calculated by applying Chi-square test to compare the groups. Results: Out of 1370, Group-A (no COVID-19) had 1055(77.0%) patients, group-B (post COVID-19) had 296(21.6%) patients and group-C (active COVID-19) had 19(1.4%) patients. Male cases were 977(71.3%) and females were 393(28.7%). 759(55.4%) patients underwent conventional CABG, 327 (23.9%) had off-pump CABG and 284 (20.7%) had valve replacement surgery. On comparing these three groups for outcome, statistically significant findings were found. Morbidity in terms of renal derangement (p